Efficacy of Preoperative Chemotherapy for High Risk Upper Tract Urothelial Carcinoma - Foerster, Beat; Abufaraj, Mohammad; Petros, Firas; Azizi, Mounsif; Gupta, Mohit; Schweitzer, Donald; Margulis, Vitaly; Iwata, Takehiro; Kimura, Shoji; Shabsigh, Ahmad; Briganti, Alberto; Ku, Ja H; et al. (The Journal of urology, 2020)
PURPOSE: The impact of preoperative chemotherapy in patients with upper urinary tract urothelial carcinoma remains poorly investigated. We assessed the rates of pathological complete response (pT0N0/X) and downstaging (pT1N0/X or less) at radical nephroureterectomy after preoperative chemotherapy and evaluated their impact on survival. MATERIALS AND METHODS: This was an international observational study of patients who underwent preoperative chemotherapy and radical nephroureterectomy for high risk upper tract urothelial carcinoma between 2005 and 2017. Multiple imputation of chained equations was applied to account for missing values. Logistic regression analyses were performed to identify predictors of pathological response. Cox proportional hazard regression models were used to estimate recurrence-free survival, cancer specific survival and overall survival. RESULTS: A total of 267 patients met our inclusion criteria. Among included patients 82 (31%) received methotrexate, vinblastine, doxorubicin and cisplatin; 123 (46%) gemcitabine and cisplatin; 25 (9%) gemcitabine and carboplatin; and 32 (12%) other regimens. The overall rates of pathological complete response and pathological downstaging were 10.1% and 44.9%, respectively. On multivariable analysis the use of gemcitabine and cisplatin, and gemcitabine and carboplatin was not statistically different from methotrexate, vinblastine, doxorubicin and cisplatin in achieving pathological complete response and pathological downstaging, respectively. The number of administered cycles did not appear to have an effect on pathological responses. Pathological downstaging was the strongest prognostic factor for recurrence-free survival (HR 0.2, p <0.001), cancer specific survival (HR 0.19, p <0.001) and overall survival (HR 0.40, p <0.001). CONCLUSIONS: Pathological downstaging after preoperative chemotherapy is a robust prognostic factor at radical nephroureterectomy and is associated with improved survival outcomes. Although preoperative chemotherapy appears to be effective, well designed prospective studies are still needed.
Keywords: Ureter; logistické modely; neoadjuvantní terapie; Humans; Risk; riziko; ureter; analýza přežití; karcinom z přechodných buněk; Chemotherapy, Adjuvant; Drug Administration Schedule; Female; Antineoplastic Agents; protokoly protinádorové kombinované chemoterapie; výsledek terapie; lidé; Survival Analysis; adjuvantní chemoterapie; transitional cell; staging nádorů; Follow-Up Studies; ženské pohlaví; neoadjuvant therapy; Male; nádory močového měchýře; Retrospective Studies; carcinoma; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Carcinoma, Transitional Cell; Neoadjuvant Therapy; protinádorové látky; nephroureterectomy; retrospektivní studie; Neoplasm Staging; Nephrectomy; mužské pohlaví; nefrektomie; Urinary Bladder Neoplasms; Logistic Models; rozvrh dávkování léků; následné studie